Analisis Komparatif Kinerja Keuangan Klien Terbesar TSMC Selama Kekurangan Chip Global: Pengejaran Panas Silikon Taiwan - Sahabat Adi Kusuma; Erman Sumirat (Politeknik Ganesha Medan, 2023)
This study aims to analyze the comparative financial performance of TSMC's largest clients during the global chip shortage phenomenon. Chip shortages have occurred since early 2020, which has pushed supply owned by chip manufacturers to have difficulty meeting demand due to the pandemic. Demand for chips that began to rise at the end of 2020 prompted chip manufacturers to increase their production due to unexpected demand. As a result, there is an impact on the financial performance of electronics companies in meeting the chip shortage. The method used in this study is a quantitative method, using the Manova one-way repeated measurement method and the Friedman test. The results show that among all the variables tested, only Net Profit Margin and Earnings per Share show changes that are significantly affected by the global chip shortage.